Re ligando os fios invisíveis da espoliação: trabalhadores do lixo e a ativação dos limites da precariedade do trabalho - Montenegro, David Moreno (2010)
According to IMPARH (2006)´s research, it is estimated that there are between 6 (six) and 8 (eight) thousand collectors of recyclable materials on the streets of Fortaleza. Individuals who subscribe their existence in the margin crumbs, living and mingling with tailings, purging of the consumer society, marked by the stigma of superfluity. A true legion of workers who pan forms of survival through residuos which, each day, rediscover the city, establish several relations in the urban environment and among other social actors with whom they interact, in a continual quest to break the morbid chains of public invisibility. In a crisis context, long term natural unemployment and capital reconcentration, these labor activities, extremely degrading, spread and gain greater visibility due to the worsening of the "social issue" because, although they represent essential activities to the survival of those who exert them, on the other hand, they play a significant role in the process of labor surplus production, appreciation and accumulation of capital, plunging the workers in a situation of increasing degradation, dispossession and misery. Thus, I consider that a large proportion of the individuals who comprise the productive chain of recycling lay on the verge of precarious employment, informality and exploitation, having little room and opportunities for social mobility or reaction. I intend, therefore, seize the work manifestation forms of men and women working immersed in the scavenging of solid waste, and the sociabilities produced in the context of growing precariousness of all social and living conditions of workers in the trash. Investigating the ways and conditions under which they develop working relations within the productive chain of recycling, considering also the process of precarious work of grooming and relationships built through the marketing of waste as the interfaces with its capitalist transformations occurring in the world of work in recent decades.